CHANDRAPUR DISTRICT AGRICULTURAL PRODUCE MARKET COMMITTEE CONDUCTED STUDY OF VARIOUS SCHEMES AND STRATEGIES FOR FARMERS. - Nagtode, Amol Sudhir; Gedam, Tatyaji K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Agriculture plays an important role in the Indian economy and farmers depend on various government schemes and policies to ensure sustainable livelihood. Agricultural Produce Market Committee (APMC) is the main regulatory body responsible for ensuring fair trading practices, price stability and market access for farmers. This study examines the various schemes and policies implemented by the Agricultural Produce Market Committee in Chandrapur district and analyzes their effectiveness in improving farmers' produce, market access and overall agricultural development. The amendment used a mixed method including primary surveys with farmers, interviews with Agricultural Produce Market Committee officials and review of policy documents. Key areas of focus include Minimum Basic Price (MSP) mechanism, subsidy programmes, infrastructure development initiatives and digitalization efforts in agricultural marketing. The findings highlight the challenges, challenges, and gaps in policy implementation while providing insights into potential improvements for a more inclusive and efficient agricultural marketing system. The objective of the study is to contribute to strategic recommendations that enhance the welfare of farmers in Chandrapur and related agricultural regions.